Lotus japonicus NOOT‐BOP‐COCH‐LIKE1 is essential for nodule, nectary, leaf and flower development. (4th May 2018) - Magne, Kévin; George, Jeoffrey; Berbel Tornero, Ana; Broquet, Blandine; Madueño, Francisco; Andersen, Stig U.; Ratet, Pascal
Summary: The NOOT‐BOP‐COCH‐LIKE ( NBCL ) genes are orthologs of Arabidopsis thaliana BLADE‐ON‐PETIOLE1/2 . The NBCLs are developmental regulators essential for plant shaping, mainly through the regulation of organ boundaries, the promotion of lateral organ differentiation and the acquisition of organ identity. In addition to their roles in leaf, stipule and flower development, NBCL s are required for maintaining the identity of indeterminate nitrogen‐fixing nodules with persistent meristems in legumes. In legumes forming determinate nodules, without persistent meristem, the roles of NBCL genes are not known. We thus investigated the role of Lotus japonicus NOOT‐BOP‐COCH‐LIKE1 ( LjNBCL1 ) in determinate nodule identity and studied its functions in aerial organ development using LORE1 insertional mutants and RNA interference‐mediated silencing approaches. In Lotus, LjNBCL1 is involved in leaf patterning and participates in the regulation of axillary outgrowth. Wild‐type Lotus leaves are composed of five leaflets and possess a pair of nectaries at the leaf axil. Legumes such as pea and Medicago have a pair of stipules, rather than nectaries, at the base of their leaves. In Ljnbcl1, nectary development is abolished, demonstrating that nectaries and stipules share a common evolutionary origin. In addition, ectopic roots arising from nodule vascular meristems and reorganization of the nodule vascular bundle vessels were observed on Ljnbcl1 nodules. This demonstrates that NBCL functions are conserved in both indeterminate and determinate nodules through the maintenance of nodule vascular bundle identity. In contrast to its role in floral patterning described in other plants, LjNBCL1 appears essential for the development of both secondary inflorescence meristem and floral meristem. Significance Statement: The Lotus japonicus LjNOOT‐BOP‐COCH‐LIKE1 ( LjNBCL1) functions are conserved for determinate nodule identity through the maintenance of nodule vascular bundle identity and for above‐ground vegetative lateral organ determinacy. Furthermore, our mutants study showed that nectary glands and stipules share a common evolutionary origin and that the Lotus japonicus LjNBCL1 gene is essential for both secondary inflorescence meristem development and promotion of the floral meristem fate determinacy.